Russian Bishop in Gilded Age America - V. V. Pechatnov; V. O. Pechatnov (Vestnik MGIMO-Universiteta, 2021)
The article deals with the American period in the life of Bishop Nickolay (Ziorov) when he was the head of the Aleutian and Alaska dioceses of the Russian Orthodox Church (1891-1898). Based on little known documents of the Holy Synod (Russian State Historical Archive) and Russian diplomatic missions in the USA (Archive of Foreign Police of the Russian Empire) the authors survey his activities to build-up the stagnant diocese and to expand Eastern Orthodoxy in the United States which prepared the ground for its renewal under his successor Bishop Tikhon (Belavin). Special attention is being paid to how American realities of the Gilded Age were perceived by a well-educated Russian priest as reflected in his diaries and travel notes that until now have avoided historians’ attention. Of special interest are Nickolay’s travel notes made during his trips around the country including his long visit to the Chicago World Fair of 1893. The Bishop’s literary talent and lively curiosity lend special flavor to these impressions creating a sense of presence. It is demonstrated that his perception was shaped both by his clergy experience and a more general framework of Russian culture. Hence an admiration of American economic and technological progress went hand in hand with a total rejection of American materialism, individualism and political values. Bishop Nickolay’s impressions of the United States constitute a revealing case study in how image of America as a constituent “the other”, the juxtaposition of the “Russian Idea” and the “American Dream” fitted into the Russian mentality.